Penetrating probability and cross section of the Li+–C60 encapsulation process through an ab initio molecular dynamics investigation. Issue 10 (22nd February 2018) - Ho, Thi H.; Kawazoe, Yoshiyuki; Le, Hung M.
Abstract : The encapsulation of Li + –C60 has been shown to be dependent on inletting kinetic energy of Li +, and shooting angle, and the minimum energy threshold for penetrating is ∼6.6 eV. Abstract : The endohedral complex system of Li + –C60 has been shown to possess interesting applications in photovoltaics, supramolecular chemistry, and functionalized materials. In this study, we perform a theoretical investigation of Li + encapsulation within a C60 cage by employing an ab initio molecular dynamics approach. The Li + cation is positioned 9 Å away from the C60 center of mass, and fired towards a randomized spot in a six-membered ring with a certain level of inletting energy, which is 7.5 eV, 9 eV, 12 eV, or 15 eV. In total, 2000 samples of MD trajectories are investigated. Our statistical results yielded a penetrating probability in the range of 0.8% to 15.6% with respect to the above inletting energy, while the cross section ranges from 0.006 Å 2 to 0.123 Å 2 . Moreover, we observed that the penetrating probability exhibited direct proportionality to the inletting energy. Hence, we can determine that the minimum required inletting energy for reaction occurrence is 6.6 eV. Overall, it seems difficult for Li + to penetrate through the sp 2 -carbon wall, because a very high inletting energy is required to open the entrance. At the same time, Li + must approach closely to the center of a six-membered ring to enhance the penetration probability.